2016
DOI: 10.1590/1518-8345.1121.2841
|View full text |Cite
|
Sign up to set email alerts
|

Music listening for anxiety relief in children in the preoperative period: a randomized clinical trial

Abstract: Objective:to investigate the effects of music listening, for 15 minutes, on the preoperative anxiety levels in children undergoing elective surgery in comparison with conventional pediatric surgical care. Method:randomized controlled clinical trial pilot study with 52 children in the preoperative period, aged 3 to 12 years, undergoing elective surgery and randomly allocated in the experimental group (n = 26) and control group (n = 26). Anxiety was assessed in both groups by the application of the modified Yale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 15 publications
0
25
0
10
Order By: Relevance
“…Prevention of anxiety, both from the patient and caregivers' perspective, was the most common primary outcome of interest, accounting for over a fifth of studies (n=20, 23%). 32,37,38,49,53,54,57,58,59,63,70,71,79,81,91,93,94,103,105,108 Prevention of anxiety was a secondary outcome of interest in a further nine (10%) studies. 22,23,25,47,50,55,69,73,80 Of the studies including anxiety prevention as the primary outcome, nine studies (47%) were focused on adult patients; 32,38,53,57,59,71,81,94,105 nine were focused on pediatric patients, 37,49,54,63,79,91,93,103,108 (with four of these also including caregivers as a sub-population, …”
Section: Prevention Of Caregiver and Patient Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention of anxiety, both from the patient and caregivers' perspective, was the most common primary outcome of interest, accounting for over a fifth of studies (n=20, 23%). 32,37,38,49,53,54,57,58,59,63,70,71,79,81,91,93,94,103,105,108 Prevention of anxiety was a secondary outcome of interest in a further nine (10%) studies. 22,23,25,47,50,55,69,73,80 Of the studies including anxiety prevention as the primary outcome, nine studies (47%) were focused on adult patients; 32,38,53,57,59,71,81,94,105 nine were focused on pediatric patients, 37,49,54,63,79,91,93,103,108 (with four of these also including caregivers as a sub-population, …”
Section: Prevention Of Caregiver and Patient Anxietymentioning
confidence: 99%
“…22,23,25,47,50,55,69,73,80 Of the studies including anxiety prevention as the primary outcome, nine studies (47%) were focused on adult patients; 32,38,53,57,59,71,81,94,105 nine were focused on pediatric patients, 37,49,54,63,79,91,93,103,108 (with four of these also including caregivers as a sub-population, 37,49,54,108 and another focused on adolescents 37 ); one study concentrated solely on caregiver (parent) anxiety. 70 The interventions of interest included music; 32,58,59,71,103 education (including videos); 37,70,81,94 visiting preoperative facilities; 54 play; 79,91,93,108 relaxation and sounds from nature; 57 aromatherapy; 53 photographic displays;…”
Section: Prevention Of Caregiver and Patient Anxietymentioning
confidence: 99%
“…Most importantly, recent studies have demonstrated that many nonpharmacological interventions prescribed by nurses are effective in anxiety reduction and control in very different settings (Al-Azawy, Oterhals, Fridlund, Assmus, & Schuster, 2015;Franzoi, Goulart, Lara, & Martins, 2016;Hosseini, Heydari, Vakili, Moghadam, & Tazyky, 2016;Saatsaz, Rezaei, Alipour, & Beheshti, 2016) and that their efficacy is similar to pharmacological treatments (Salmore & Nelson, 2000). Moreover, Peplau's therapeutic communication has proved effective in reducing anxiety among patients (Zarea, Maghsoudi, Dashtebozorgi, Hghighizadeh, & Javadi, 2014).…”
Section: A Brief Reflection On Interventions To Reduce Anxietymentioning
confidence: 99%
“…Destaca-se ainda o potencial terapêutico da música para atuar diretamente na redução da pressão arterial e frequência cardíaca 17 , além de auxiliar na redução da dor e da ansiedade em crianças submetidas a procedimentos cirúrgicos 18 . As intervenções com música podem também auxiliar significativamente na redução de estresse, ansiedade, dor, medo e angústia 3 .…”
Section: Estimulando O Brincar Através Da Músicaunclassified
“…A redução de agravos relaciona-se principalmente à redução da ansiedade, dor, estresse, e à ampliação do vínculo e dos processos de comunicação, sobretudo quando a criança está submetida a procedimentos cirúrgicos 18 . Nessa perspectiva, é importante destacar que promover suporte a expressão de sentimentos é um dos elementos do CP que sustentaram a atividade, além de outro elemento que se refere a estar autenticamente presente para possibilitar a expressão da subjetividade do outro 10 .…”
Section: Promovendo Bem-estar a Partir De Alterações Positivas Da Músicaunclassified